Growth and Osteogenic Differentiation of Discarded Gingiva-Derived Mesenchymal Stem Cells on a Commercial Scaffold - Cristaldi, Marta; Mauceri, Rodolfo; Campisi, Giuseppina; Pizzo, Giuseppe; Alessandro, Riccardo; Tomasello, Laura; Pitrone, Maria; Pizzolanti, Giuseppe; Giordano, Carla (Frontiers in Cell and Developmental Biology, 2020)
Background: In periodontal patients with jaw bone resorption, the autologous bone graft is considered the “gold standard” procedure to allow the placement of dental prosthesis, resulting in higher costs of interventions and risks of clinical complications. Thanks to the use of adult mesenchymal stem cells, smart biomaterials and active biomolecules, regenerative medicine and bone tissue engineering represent a valid alternative to the traditional procedures. Aims: Testing the osteoconductive activity of FISIOGRAFT Bone Granular® and Matriderm® collagen scaffolds on mesenchymal stem cells isolated from periodontally-compromised gingiva, up to now considered a biological waste and discarded during surgical procedures, to develop a low-cost and painless strategy of autologous bone tissue regeneration. Materials and Methods: We isolated human mesenchymal stem cells from 22 healthy and 26 periodontally-compromised gingival biopsy tissues and confirmed the stem cell phenotype by doubling time assay, colony-forming unit assay and expression of surface and nuclear mesenchymal stem cell markers, respectively by cytofluorimetry and Real Time-quantitative PCR. Healthy and periodontally-compromised gingival mesenchymal stem cells were seeded on FISIOGRAFT Bone Granular® and Matriderm® scaffolds and in vitro cell viability and bone differentiation were then evaluated. Results: Even though preliminary, the results demonstrate that FISIOGRAFT Bone Granular® is not suitable for in vitro growth and osteogenic differentiation of healthy and periodontally-compromised mesenchymal stem cells, which, instead, are able to grow, homogeneously distribute and bone differentiate in the Matriderm® collagen scaffold. Conclusions: Matriderm® represents a biocompatible scaffold able to support the in vitro cell growth and osteodifferentiation ability of gingival mesenchymal stem cells isolated from waste gingiva, and could be employed to develop low-cost and painless strategies of autologous bone tissue regeneration.